A model-scale experimental and theoretical study on a mineral oil-immersed battery cooling system. (December 2022) - Liu, Jiahao; Fan, Yining; Wang, Jinhui; Tao, Changfa; Chen, Mingyi
Abstract: The concept of immersion cooling has been proposed and validated via several numerical studies in recent years, while systematical experimental studies and corresponding theoretical considerations on its heat transfer mechanism are scarcely available in the literature. In this work, a series of experiments are conducted by means of a well-designed model-scale oil-immersed battery cooling system to explore the thermal behavior of a dynamically cycling battery subjected to static and flowing mineral oil (MO). The battery temperature can be maintained below 35 °C for 5 mL/min flow rate, and below 30 °C when exceeding 15 mL/min, even at 4 C discharge rate. Increasing MO flow rate can reduce the battery temperature, while this effect gradually attenuates due to the cooling capacity limit of the system. The theoretical analysis verifies that the dominated heat transfer mechanism varies with both battery cycle rate and Reynolds number of the fluid. The rising cycle rate can enlarge the natural convection dominated range, and at 4 C cycle rate, the natural convection even dominates in currently entire Re range. The findings here quantitatively and theoretically confirm the effectiveness of the oil-immersed battery cooling system, which provides more new insights into the development of practical immersion cooling system.